The Effect of Financial Performance and Environmental Costs toward Environmental Performance in Coal-Mining Companies Listed on the Indonesia Stock Exchange 2015-2018 - Karima Fibriani; Taufiq Taufiq; Yusnaini Yusnaini (Облік і фінанси, 2020)
The purpose of this study is to provide empirical evidence regarding the effect of financial performance and environmental costs on environmental performance. In this study, the financial performance is calculated by the liquidity ratio, leverage ratio, and profitability ratio. Liquidity ratios are represented in the current ratio (CR) and the quick ratio (QR). Then, in this study, the leverage ratio is represented in debt to asset ratio (DAR) and the debt to equity ratio (DER). Profitability ratios in this study are represented in net profit margin (NET), the return of investment (ROI), and the return of equity (ROE). The environmental costs in this study were calculated using the rehabilitation provision, reclamation, and mining closure divided by earnings after tax (EAT). The environmental performance was calculated based on the results of the PROPER rating issued by the Environmental Ministry. This study uses secondary data. Itmeans that the researchers obtain data by accessing financial statements and annual reports of company objects.It collects on the Indonesia Stock Exchange (IDX) website and the official website of each company. This study uses a panel data regression technique that combines cross-section and time-series data. Therefore, the results showed that the liquidity ratio in financial performance and leverage ratio in financial performance affect environmental performance. In contrast, theprofitability ratios in financial performance and environmental costs do not affect environmental performance.